MOTIVASI KERJA DAN LINGKUNGAN KERJA MEMPENGARUHI KEPUASAN KERJA KARYAWAN DI PT INDOMARCO PRISMATAMA (Studi Kasus Indomaret Kota Depok) - Maulana, Irvan; Nurlina, Ida (Journal of Research and Publication Innovation, 2024)
This research was conducted to determine the impact of work motivation and work environment on employee job satisfaction at PT Indomarco Prismatama (a case study of Indomaret in Depok City), both partially and simultaneously. The research method used was quantitative associative. The sample comprised 67 respondents obtained through a saturated sampling technique. The types of data used included primary and secondary data, collected through observation, interviews, questionnaires, and literature studies. Data analysis techniques included data instrument tests, classical assumption tests, simple and multiple linear regression tests, correlation and determination coefficient tests, and partial and simultaneous hypothesis tests. The results showed that work motivation has a positive and significant effect on employee job satisfaction, with a significance value of 0.000<0.05 and a t-value of 4.145>1.997. The work environment also has a positive and significant effect on employee job satisfaction, with a significance value of 0.000<0.05 and a t-value of 5.987>1.997. Simultaneously, work motivation and work environment have a positive and significant effect on employee job satisfaction, with a significance value of 0.000<0.05 and an F-value of 267.424>3.14. Work motivation and work environment simultaneously also have a determination level of 89.3%.